Morphological and chemical differences within superheater deposits from different locations of a black liquor recovery boiler. (15th March 2023) - Balint, Roland; Engblom, Markus; Niemi, Jonne; Lindberg, Daniel; Saarinen, Timo; Rautala, Jaakko; Hupa, Mikko; Hupa, Leena
Abstract: The effects of two deposit ageing mechanisms were identified by analysing superheater ash deposits from a kraft recovery boiler. Local differences in deposit morphology and chemical composition were identified under the electron microscope. Temperature-gradient-induced diffusion of alkali chloride vapours toward the steel was evident. Two deposit types were identified, based on local chemical compositions: "Type 1" deposits had an innermost porous layer of fine, sintered fume particles enriched in K and Cl, that deposited after homogeneous condensation in the gas phase. "Type 2" deposits formed via sulfation of initially deposited fume particles rich in K and Cl. Thus the innermost layer was enriched in K and S, while concurrently depleted in Cl. Differences in the local first melting temperature (T0 ) within the innermost regions of the two deposit types were identified. T0 reached a minimum within the innermost region of Type 1 deposits, implying an increased risk for melt formation and corrosion. Whereas for Type 2 deposits, T0 was increased closest to the steel, reducing the risk for melt formation and superheater corrosion. The presented results provide a better understanding of intra-depositional changes taking place after initial deposition, helping assess risks of deposit-related operational problems in the boiler. Highlights: Differences in morphology and chemical composition depending on sampling location. Morphological differences in deposits affect ageing behaviour. Concurrent enrichment in K and Cl lowers local first melting temperature. Sulfation of innermost deposit region increases local first melting temperature.